2019
DOI: 10.1620/tjem.249.185
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Characterization of the External Carotid Artery: Special Attention to Variations in Branching Patterns

Abstract: Knowledge of branching patterns of external carotid artery (ECA) is essential for planning and execution of head and neck surgeries. Digital subtraction angiography (DSA) images of 532 ECAs from 302 consecutive patients were retrospectively evaluated. We classify the branch variants of ECA into three types, simply based on the number of branches arising close together. Type A, Type B, and Type C variants are defined as two, three, and four or more branches of ECAs arising at a common point from the proximal EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The occlusion of R ECA was successfully visualized, as contrast distribution was no longer observed past the location of the clot (dotted line, Figure S7). In the control tissue, the left external, internal, and common carotid arteries (L ECA, L ICA, and L CCA, respectively) were all clearly visible, due to the presence of dark contrast which highlighted the characteristic branching of ECA. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occlusion of R ECA was successfully visualized, as contrast distribution was no longer observed past the location of the clot (dotted line, Figure S7). In the control tissue, the left external, internal, and common carotid arteries (L ECA, L ICA, and L CCA, respectively) were all clearly visible, due to the presence of dark contrast which highlighted the characteristic branching of ECA. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In the control tissue, the left external, internal, and common carotid arteries (L ECA, L ICA, and L CCA, respectively) were all clearly visible, due to the presence of dark contrast which highlighted the characteristic branching of ECA. 5,52,53 Again, it is important to consider the characteristics of the clots being used in these experiments. All clots were made using whole blood with regular circulating concentrations of fibrinogen (2−5 mg/mL), which formed red blood cell (RBC)-rich blood clots.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a study of 302 patients, Yamamoto et al determined the incidences of ECA branching patterns by analyzing 532 ECAs using digital subtraction angiography. They classified these arteries into three categories (A, B, C) based on the number of branches (two, three, four or more) emerging from the proximal ECA at a common point, the distal ECA counting as one branch [14]. Using this criterion, Type A (two branches) is defined as all individual branches arising separately from the proximal ECA.…”
Section: Other Anatomical Variations Of the Branches Of The Ecamentioning
confidence: 99%
“…They also found that 96.3% of Type C ECAs had a CCA bifurcation at the level of the junction of the thirdfourth cervical vertebrae or higher, which was significantly higher than the bifurcation in Type A or B. Because there are several anatomical variations, it is imperative that surgeons be aware of the Type C variation to avoid unexpected complications [14] An anatomical variation of the ascending palatine artery, branching from the lingual artery instead of the facial artery, has been noted in previous literature. Unfortunately, we could find no more details of this variation [11].…”
Section: Other Anatomical Variations Of the Branches Of The Ecamentioning
confidence: 99%
“…As above, the incubations were left to equilibrate for 45-minutes with FB139-AuNPs, iopamidol, and all clearly visible, due to the presence of dark contrast which highlighted the characteristic branching of ECA. 152,231,232 Again, it is important to consider the characteristics of the clots being used in these experiments. All clots were made using whole blood with regular circulating concentrations of fibrinogen (2-5 mg/mL), which formed red blood cell (RBC)-rich blood clots.…”
Section: Fa-aunp Computed Tomography (Human Blood)mentioning
confidence: 99%